2011
DOI: 10.1111/j.1551-2916.2011.04559.x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Materials to Expand the Boundaries of Material‐Property Space

Abstract: The materials we use today for mechanical design are the outcome of at least 3000 years of development, much of it empirical but much the outcome of systematic science. Both approaches have been motivated by the desire for stiffer, stronger, more durable, and lighter structures, progressively populating material property “space”. We first examine the extent to which this space is now filled and estimate the ultimate constraints on this filling. Strategies for expanding the filled regions further include hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 10 publications
0
53
0
Order By: Relevance
“…Excellent agreement between model and simulation is obtained. (3) Provided understanding of the high rate loading (constant rate) of TIM assemblies. We have found that the principle underlying mechanism of the formation of force chains is again present, albeit somewhat mitigated if slip is considered.…”
Section: Inventions (Dd882) Scientific Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent agreement between model and simulation is obtained. (3) Provided understanding of the high rate loading (constant rate) of TIM assemblies. We have found that the principle underlying mechanism of the formation of force chains is again present, albeit somewhat mitigated if slip is considered.…”
Section: Inventions (Dd882) Scientific Progressmentioning
confidence: 99%
“…Hybrid material systems are understood to provide efficient alternatives to conventional materials and fill holes in material property spaces [1][2][3]. One of the methods relevant for the creation of hybrid material systems is that of segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of the skins by the core increases the moment of inertia of the section and its section modulus producing a structure that resists bending and buckling loads well. Correspondingly, the core has to be stiff enough to ensure the skins do not slip over each other and make the sandwich structure behave as a load-bearing unit (Ashby, 2011). An adhesive layer also provided in a sandwich structure to assure the core and skins are bonded together.…”
Section: Sandwich Composite Structuresmentioning
confidence: 99%
“…The separation of the skins (faces), which actually carry the load, by a low density core, increases the moment of inertia of the panel with little increase in weight producing an efficient structure (Ashby, 2011). The studies on sandwich structures have been extensively continued due to the advantages in sandwich structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation